Bioassinaturas: uma proposta de astrobiologia para educação básica e a nova BNCC. - SANTOS, Tainah Campelo (2024)
The distance among the school subjects about natural sciences makes it impossible to fully understand the phenomena that permeate everyday life, affecting students' history learning, since these events do not occur in an isolated way, in other words, they are not specific to the area of Physics, Chemistry or Biology. However, inserting interdisciplinary practice, in this context, taking into account the school environment raises a series of challenges that surround mainly the preparation of teachers, highlighting the need to reinvent themselves in this scenario. Thus, the use of Astrobiology as a transversal theme to Natural Sciences can contribute to the development of essential teaching and learning based on the interdisciplinarity among concepts present in natural sciences in order to fulfill the gaps left in basic education due to a fragmented teaching, as well as helping basic education teachers in creating a guiding work plan. In this way, the present study aims to present an alternative work for the teaching staff in order to contribute to interdisciplinary and transdisciplinary practice, associating contents related to the study of biosignatures, in order to integrate the disciplines of natural sciences to work in conjunction with the high school curriculum. Therefore, this research sought to identify and link common study topics between Astrobiology and science teaching through document analysis of the National Common Curricular Base (BNCC) identifying and grouping the structuring themes in order to develop a world view in students and to provide a broader and more contextualized knowledge of phenomena from an integrated perspective of Physics, Chemistry and Biology. Thus, it is hoped that this work will be able to guide basic education teachers through an interdisciplinary proposal that can be incorporated into their lesson planning without change the established objects of knowledge, providing a motivating environment that favors the development of the skills and competences necessary for students’ education.